Spatiotemporal Patterns of Contact Across the Rat Vibrissal Array During Exploratory Behavior - Hobbs, Jennifer A.; Towal, R. Blythe; Hartmann, Mitra J. Z. (Frontiers in Behavioral Neuroscience, 2016)
The rat vibrissal system is an important model for the study of somatosensation, but the small size and rapid speed of the vibrissae have precluded measuring precise vibrissal-object contact sequences during behavior. We used a laser light sheet to quantify, with 1 ms resolution, the spatiotemporal structure of whisker-surface contact as five naïve rats freely explored a flat, vertical glass wall. Consistent with previous work, we show that the whisk cycle cannot be uniquely defined because different whiskers often move asynchronously, but that quasi-periodic (~8 Hz) variations in head velocity represent a distinct temporal feature on which to lock analysis. Around times of minimum head velocity, whiskers protract to make contact with the surface, and then sustain contact with the surface for extended durations (~25 – 60 ms) before detaching. This behavior results in discrete temporal windows in which large numbers of whiskers are in contact with the surface. These “sustained collective contact intervals” (SCCIs) were observed on 100% of whisks for all five rats. The overall spatiotemporal structure of the SCCIs can be qualitatively predicted based on information about head pose and the average whisk cycle. In contrast, precise sequences of whisker-surface contact depend on detailed head and whisker kinematics. Sequences of vibrissal contact were highly variable, equally likely to propagate in all directions across the array. Somewhat more structure was found when sequences of contacts were examined on a row-wise basis. In striking contrast to the high variability associated with contact sequences, a consistent feature of each SCCI was that the contact locations of the whiskers on the glass converged and moved more slowly on the sheet. Together, these findings lead us to propose that the rat uses a strategy of “windowed sampling” to extract an object’s spatial features: specifically, the rat spatially integrates quasi-static mechanical signals across whiskers during the period of sustained contact, resembling an “enclosing” haptic procedure.